2023
DOI: 10.1021/acsomega.3c01413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Antimicrobial, Density Functional Theory, and Molecular Docking Studies of Novel Mn(II), Fe(III), and Cr(III) Complexes Incorporating 4-(2-Hydroxyphenyl azo)-1-naphthol (Az)

Abstract: This work synthesized three new CrAz2, MnAz2, and FeAz2 complexes and investigated them using IR, mass, UV spectroscopy, elemental analysis, conductivity and magnetic tests, and thermogravimetric analysis. The azo-ligand, 4-(2-hydroxyphenylAzo)-1-naphthol (Az), couples with metal ions via its nitrogen (in −NN– bonds) and oxygen (in hydroxyl group) atoms, according to the IR spectra of these complexes. Through thermal examination (TG/TGA), the number and location of water in the complexes were also determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 93 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…The E LUMO values of −2.3997, −1.8806, and −0.7115 eV depict these respective energy states. The Δ E gap of 3.2230 eV is indicative of the molecule’s kinetic stability, with a small gap suggesting promising reactivity in comparison to 4.55 eV for Sorafenib, 4.19 eV for Erlotinib, and 7.22 eV for Lenvatinib. Moreover, the chemical hardness (η) of 1.6115 eV highlights the molecule’s resistance to electron exchange and its overall stability. Specifically, it quantifies the energy required to add or remove an electron from the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E LUMO values of −2.3997, −1.8806, and −0.7115 eV depict these respective energy states. The Δ E gap of 3.2230 eV is indicative of the molecule’s kinetic stability, with a small gap suggesting promising reactivity in comparison to 4.55 eV for Sorafenib, 4.19 eV for Erlotinib, and 7.22 eV for Lenvatinib. Moreover, the chemical hardness (η) of 1.6115 eV highlights the molecule’s resistance to electron exchange and its overall stability. Specifically, it quantifies the energy required to add or remove an electron from the system.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the sulfur atom (S-22) in the molecule exhibits a negative charge (−0.4902 a.u. ), suggesting an excess of electrons in its vicinity . This negative charge on sulfur may be a consequence of its participation in various resonance structures or interactions with neighboring atoms, leading to the localization of ED …”
Section: Resultsmentioning
confidence: 99%
“…The chemical potential, denoted as CP, is the negative value of the electronegativity (CP = −χ). Chemical hardness (η) and softness (σ): η = (IP – EA)/2, σ = 1/2η, respectively . The electrophilicity index, ω, and nucleophilicity index, Nu, are determined as ω = (CP 2 )/(2η), and Nu = 1/ω, respectively .…”
Section: Methodsmentioning
confidence: 99%
“…HOMO-LUMO energy gap is the evidence for reactivity, stability and even biological potential and serves as the source for the calculation of reactivity parameters. 54 The lowest energy gap values indicate the highest reactivity, polarizability and, hence, highest biological potential. 52 According to this, it is found that the metal complexes exhibit the highest pharmacological activity than the ligand.…”
Section: Optimized Structures Of the Compoundsmentioning
confidence: 99%